Critical Investigation of Novel Computational Techniques for Automated Valuations of Real Estate Properties in Cyprus - Dimopoulos, Thomas (Department of Civil Engineering and Geomatics, Faculty of Engineering and Technology, Cyprus University of Technology, 2020)
Mass appraisals for valuation purposes using automated systems have gained a lot of traction in recent years, a fact which is highlighted when viewing the large amount of corresponding literature that has become available over the past decade. The main valuation governing bodies (IAAO, RICS, IVS, TEGOVA, national authorities, etc.) have all produced papers and articles referring to the models and systems that are used for mass valuations (Computer Assisted Mass Appraisals - CAMA, Automated Valuation Models - AVM, etc.) and how their application could be revolutionary within the sector. While automated systems are already being used in many countries and jurisdictions for taxation purposes, the demand for mass appraisals is growing as a result of the financial globalization process. Issues regarding ethics, licensing and responsibility of the valuations produced by automated systems remain pending but are being addressed constantly, as well as their importance and impact on the broader environment of valuation practice and the Real Estate industry. The aim of this PhD thesis is to provide a rigorous and accurate analysis of the mass appraisal procedure, to highlight the relevant techniques and methodologies, and to propose innovative methods to advance the currently used mass appraisal system in Cyprus through worked case studies based also from the literature review findings. A global history of mass appraisals, as well as definitions, methodologies and models’ specifications, calibration and adjustments are presented and the most common applications of mass appraisals are discussed. The models implemented by the Cyprus Department of Lands and Surveys (DLS) for taxation purposes are analyzed and the strengths and weaknesses of current systems are presented and assessed. The author uses an enhanced apartments’ database to analyze the dependence on their deviation on the other parameters influencing a property’s value (covered area, location, etc.). The results of the case studies that were carried out in Nicosia (Cyprus) and Thessaloniki (Greece) using Geographically Weighted Regression, Ordinary Least Squares, Random Forests as well as other mathematical techniques are presented, scrutinized and interpreted. The author provides novel recommendations for the improvement of the models and how their application could be implemented in the wider market. Finally, he provides a critical judgment of the models’ accuracy, by utilizing both his significant professional experience (with more than 15,000 valuations conducted throughout a 15-year career) on specific test cases and real valuation practice, with a focus on outliers and observations with high errors. The main outcome of this Ph.D. is its contribution to the appropriateness of utilization of automated systems in the valuation procedure and in the broader property valuation environment based on the critical evaluation of the existing techniques and their implementation within the Cyprus region. Although the AMVs have many advantages and can be used in several sectors, they also present limitations on the real-world application. However, the use of AVMs can improve the quality of the valuation precision and lead to a higher achieved accuracy ratio per valuation, which could, in turn, create higher profits for any valuer, stakeholder and to the broader industry as well. In conclusion, mass appraisals are cost and time effective and a positive contribution to the sustainability of the broader economic and financial environment.
Keywords: CAMA; AVM; Mass Appraisals; Valuation; Property taxation; CAMA; AVM; Μαζικές Εκτιμήσεις; Εκτίμηση; Φορολογία Ακινήτων